2019
DOI: 10.1002/tox.22696
|View full text |Cite
|
Sign up to set email alerts
|

Zearalenone induces apoptosis of rat Sertoli cells through Fas‐Fas ligand and mitochondrial pathway

Abstract: Zearalenone (ZEA) is an estrogen-like toxin produced by Fusarium that is widely found in cereals worldwide. In recent years, ZEA has been found to cause reproductive dysfunction in male animals, but the underlying mechanism remains unclear. This study examined the apoptosis of rat Sertoli cells induced by different concentrations (0, 5, 10, and 20 μmol/L) of ZEA via Fas-Fas ligand and mitochondrial signaling pathway in vitro. Apoptosis rate was detected by flow cytometry. The mitochondrial membrane potential w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…The results suggested that BPS exposure upregulated the protein expression of Fas and FasL in the testes. Furthermore, previous studies have demonstrated that caspase‐8 plays a very important role in the apoptotic cascade signal transduction in the apoptosis mediated by the Fas/FasL pathway (Cai et al, 2019). This result is consistent with our study in which BPS induced an increase in cleaved caspase‐8 protein expression in testes.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that BPS exposure upregulated the protein expression of Fas and FasL in the testes. Furthermore, previous studies have demonstrated that caspase‐8 plays a very important role in the apoptotic cascade signal transduction in the apoptosis mediated by the Fas/FasL pathway (Cai et al, 2019). This result is consistent with our study in which BPS induced an increase in cleaved caspase‐8 protein expression in testes.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Zheng et al [89], found that low doses of zearalenone (0.01, 0.02, 0.03, 0.04, and 0.05 µmol/L) stimulated cell viability of TM3 cells (Leydig cells) measured by using the xCELLigence real-time cell analysis. Also, under the action of ZEA (20µM), cell viability of Sertoli cells derived from Male Wistar, which are important for male reproductive system, increased over control [102].…”
Section: Effect Of Zearalenone On Cellular Immune Responsementioning
confidence: 99%
“…In the present study, we demonstrated that even at low levels (1 µmol/L), ZEN can impair the in vitro development of preantral follicles, but this negative impact is minimised when these follicles are simultaneously exposed to ZEN and equol. Previous in vitro studies have showed that ZEN inhibits testosterone production by AM-10 Leydig cells (8 µmol/L) [29], increases the apoptosis rate in rat Sertoli cells (5 µmol/L) [30], affects gene expression in granulosa cells from mouse (30 µmol/L) and sows (10 µmol/L) [31], and impairs bovine oocyte maturation (1 mmol/L) [32] and porcine blastocyst rates (5 µmol/L) [33]. Although most of these concentrations are far higher than those tested in the present study, comparisons cannot be performed due to the differences of cell types and animal species.…”
Section: Discussionmentioning
confidence: 99%